2013
DOI: 10.1111/ctr.12256
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, crossover pharmacokinetic study comparing generic tacrolimus vs. the reference formulation in subpopulations of kidney transplant patients

Abstract: An exploratory, post hoc analysis was performed using data from a prospective, multicenter, open-label, randomized, two-period (14 d per period), two-sequence, crossover, steady-state pharmacokinetic study comparing generic tacrolimus (Sandoz) vs. reference tacrolimus in stable renal transplant patients receiving their pre-study twice-daily dose. Pharmacokinetic parameters were compared in 68 patients according to gender, African American ethnicity, the presence or absence of diabetes, and use of steroids. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…In this study, approximately one-third of tacrolimus users had evidence of a switch between tacrolimus manufacturers, often with a protracted delay in tacrolimus TDM testing after the switch. While studies have shown that patients can be safely managed in a controlled environment over the shortterm using any approved tacrolimus formulation 20 , the literature is devoid of reports that are representative of the realworld setting in which patients may be cycled through products from multiple manufacturers. Even less clear is what happens to these patients over longer time-horizons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, approximately one-third of tacrolimus users had evidence of a switch between tacrolimus manufacturers, often with a protracted delay in tacrolimus TDM testing after the switch. While studies have shown that patients can be safely managed in a controlled environment over the shortterm using any approved tacrolimus formulation 20 , the literature is devoid of reports that are representative of the realworld setting in which patients may be cycled through products from multiple manufacturers. Even less clear is what happens to these patients over longer time-horizons.…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic benefit of tacrolimus TDM (i.e. avoiding toxicity) is well established [8][9][10]12,15,20 . Although there are no guidelines to definitively inform the appropriate frequency of tacrolimus TDM, guidance exists regarding its necessity, particularly after a medication change or a change in a patient's status 14 .…”
Section: Discussionmentioning
confidence: 99%
“…AUC 0-12 , area under the plasma concentration versus time curve from zero to 12 hr; CI, confidence interval; C max , maximum whole blood concentration; T max , time to C max ; C 0 , concentration before the dose; Tac, tacrolimus. Bioequivalence in different age groups was unfortunately not investigated in the subpopulation analysis of the study by Alloway et al 16,24 The reasons for the observed lack of bioequivalence between the two Tac formulations remain to be investigated, and further studies should examine bioequivalence of NTI drugs in different subpopulations (e.g., age, race, and organ transplanted). Use of generic Tac resulted in a significantly higher systemic drug exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the variability margins allowed do not ensure bioequivalence for drugs with a narrow therapeutic window, such as immunosuppressive agents.In immunosuppressive drugs and in order to demonstrate the bioequivalence of generic drugs, exhaustive and rigorous studies must be performed in patients with transplantation to prove their effectiveness, as have been conducted in other countries 4,5 .…”
Section: Tacrolimusmentioning
confidence: 99%